Comparative study of expandable cage with integrated plate versus non expandable cage in cervical spine corpectomies - Pahwa, Nakul; Saha, Suniti Kumar; Roy, Kaushik; Pathak, Debajyoti; Bandyopadhyay, Shuvayu (Asian Journal of Medical Sciences, 2020)
Background: The use of expandable cages in cervical spine has gained popularity over the last decade. They have been used in dorsal spine since long but were rarely used in cervical spine due to their high cost. Now, with more insight into their mechanics, many advantages have been noted over the fixed cages along with similar efficacy and with no added complications. Aims and Objectives: To study the benefits of expandable cage with incorporated anterior cervical plate over non expandable cage in cervical spine corpectomies. Materials and Methods: Ten cases of two level corpectomy were operated in each group and compared for intraoperative time, postoperative fusion rates and complications. Results: Intraoperative time was less in the expandable cage group. Fusion rates were comparable at 6 month follow up. No reported long term complication in both groups. Conclusion: Expandable cages are less frequently used in cervical spine due to their significantly higher cost but there are advantages such as decreased intraoperative manipulation and operative time, less damage to end plates and also useful in cases of poor bone quality.